2020
DOI: 10.1037/spy0000191
|View full text |Cite
|
Sign up to set email alerts
|

The use of rational emotive behavior therapy (REBT) to increase the self-determined motivation and psychological well-being of triathletes.

Abstract: Rational Emotive Behaviour Therapy (REBT) and its relationship with self-determined motivation has received scant research attention despite growing interest in the motivational effects of REBT with athletes. Recent evidence suggests that reductions in irrational beliefs brought about by REBT may facilitate increases in self-determined motivation. The current study seeks to replicate and build this initial research using an idiographic single-case design to assess the effects of one-to-one REBT on the irration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 85 publications
(139 reference statements)
6
40
0
Order By: Relevance
“…Hence, if irrational beliefs represent a less self-determined, more controlled, types of motivation (introjected regulation), REBT should have the potential to improve self-determined motivation, as it focuses on disputing and restructuring irrational beliefs. Indeed, Turner and Davis (2018) found that self-determined motivation was increased in triathletes after an REBT education intervention and have subsequently repeated this finding using one-to-one REBT in a multi-participant idiographic case-study design (Davis & Turner, 2019). The potential dual benefits of REBT for reducing irrational beliefs and increasing self-determined motivation is important because behavioral actions that are controlled by external motives and can lead to dysfunctional behavior, such as wanting to, or actually, avoiding or escaping the current situation (Dryden & Branch, 2008;Ryan & Deci, 2002).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Hence, if irrational beliefs represent a less self-determined, more controlled, types of motivation (introjected regulation), REBT should have the potential to improve self-determined motivation, as it focuses on disputing and restructuring irrational beliefs. Indeed, Turner and Davis (2018) found that self-determined motivation was increased in triathletes after an REBT education intervention and have subsequently repeated this finding using one-to-one REBT in a multi-participant idiographic case-study design (Davis & Turner, 2019). The potential dual benefits of REBT for reducing irrational beliefs and increasing self-determined motivation is important because behavioral actions that are controlled by external motives and can lead to dysfunctional behavior, such as wanting to, or actually, avoiding or escaping the current situation (Dryden & Branch, 2008;Ryan & Deci, 2002).…”
mentioning
confidence: 87%
“…In line with similar past research (Davis & Turner, 2019), the entire American football squad (n = 25) were screened to determine which participants would take part in the REBT intervention. The screening included the German version of the Sport Motivation Scale-28 (SMS-28;Burtscher, Furtner, Sachse, & Burtscher, 2011), and the German translated version of the irrational Performance Beliefs Inventory-2 (iPBI-2; .…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion that intrinsically, rather than extrinsically, regulated motivation is more beneficial for wellbeing is echoed in what Ellis writes here. Indeed, recent research (Davis and Turner, 2019;Turner and Davis, 2018) has demonstrated that REBT can be successfully used to promote greater self-determined motivation, intimating a positive relationship between irrational beliefs and less self-determined (more controlling) motivation.…”
Section: Introductionmentioning
confidence: 99%
“…REBT delivered over three to five sessions is commonplace in the literature, and the structure of those interventions all follow the same process as that described in Table 1 (Davis & Turner, 2019;Deen, Turner, & Wong, 2017;Turner & Barker, 2013;Wood, Barker, Turner, & Sheffield, 2018). Meetings took place in a quiet corner of a local coffee shop.…”
Section: Interventionmentioning
confidence: 99%